Traumatic Neuropathic Pain - Raihan Lutfia, Lisa; Ananda Audia Arsiazi, Baiq; Hanan Farihah, Inas; Mahfuzzahroni, M (Jurnal KESANS : Kesehatan dan Sains, 2022)
Peripheral neuromas caused by trauma or injury and surgical procedures can cause traumatic neuropathic pain, functional impairment and psychological distress, which can lead to decreased quality of life. Traumatic neuropathic pain can cause the patient to feel a burning, stabbing, stinging and nauseating sensation. Based on studies, the incidence of neuropathic pain due to peripheral nerve injury varies from 2.8 to 5% in the population. Estimates of the incidence of chronic postoperative neuropathic pain vary depending on the type of surgery and surgical technique. Various techniques for the prevention and treatment of traumatic neuromas have been recommended, including massage therapy, electrical stimulation, lipofilling, methods of transposition of nerve endings into muscle, bone or vein, and confining the injured nerve with synthetic or biological materials. The challenge in the treatment of traumatic neuromas today is that patients are resistant to analgesics, so standardized treatment is needed. Conclusion : The current challenge in the treatment of traumatic neuromas is that patients are resistant to analgesics, so standardized treatment is needed.